The sabre in 19th century Greece - George Zacharopoulos (Acta Periodica Duellatorum, 2020)
This article gives a brief overview on Greek sabre sources with a special focus on Philipp Müller’s and Nikolaos Pyrgos’ treatises. The article does not aim to give a complete list of treatises neither to analyze the any of the mentioned books in details – rather it aims to give an insight in those two books which might have had the most important impact on the development of the Greek sabre fencing in the 18th and 19th Centuries.